Head‐Neck Osteoplasty has Minor Effect on the Strength of an Ovine Cam‐FAI Model: In Vitro and Finite Element Analyses. Issue 12 (December 2016) - Maquer, Ghislain; Bürki, Alexander; Nuss, Katja; Zysset, Philippe K.; Tannast, Moritz
Abstract: Background: Osteochondroplasty of the head‐neck region is performed on patients with cam femoroacetabular impingement (FAI) without fully understanding its repercussion on the integrity of the femur. Cam‐type FAI can be surgically and reproducibly induced in the ovine femur, which makes it suitable for studying corrective surgery in a consistent way. Finite element models built on quantitative CT (QCT) are computer tools that can be used to predict femoral strength and evaluate the mechanical effect of surgical correction. Questions/purposes: We asked: (1) What is the effect of a resection of the superolateral aspect of the ovine femoral head‐neck junction on failure load? (2) How does the failure load after osteochondroplasty compare with reported forces from activities of daily living in sheep? (3) How do failure loads and failure locations from the computer simulations compare with the experiments? Methods: Osteochondroplasties (3, 6, 9 mm) were performed on one side of 18 ovine femoral pairs with the contralateral intact side as a control. The 36 femurs were scanned via QCT from which specimen‐specific computer models were built. Destructive compression tests then were conducted experimentally using a servohydraulic testing system and numerically via the computer models. Safety factors were calculated as the ratio of the maximal force measured in vivo by telemeterized hip implants during the sheep's walking and running activities to the failure load. The simulated failure loads and failure locations from the computer models were compared with the experimental results. Results: Failure loads were reduced by 5% (95% CI, 2%‐8%) for the 3‐mm group (p = 0.0089), 10% (95% CI, 6%‐14%) for the 6‐mm group (p = 0.0015), and 19% (95% CI, 13%‐26%) for the 9‐mm group (p = 0.0097) compared with the controls. Yet, the weakest specimen still supported more than 2.4 times the peak load during running. Strong correspondence was found between the simulated and experimental failure loads (R 2 = 0.83; p < 0.001) and failure locations. Conclusions: The resistance of ovine femurs to fracture decreased with deeper resections. However, under in vitro testing conditions, the effect on femoral strength remains small even after 9 mm correction, suggesting that femoral head‐neck osteochondroplasty could be done safely on the ovine femur. QCT‐based finite element models were able to predict weakening of the femur resulting from the osteochondroplasty. Clinical Relevance: The ovine femur provides a seemingly safe platform for scientific evaluation of FAI. It also appears that computer models based on preoperative CT scans may have the potential to provide patient‐specific guidelines for preventing overcorrection of cam FAI.